KONTRIBUSI RETRIBUSI PASAR DALAM PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN TABANAN - I Ketut Suprapta Adi; I Made Pujawan (Kertha Negara : Journal Ilmu Hukum, 2014)
This research entitled “contribution of market retribution in improving own source revenue of Tabanan district” which becomes problem of the research is the own source revenue of Tabanan district comes from retribution which one of them is market. Based on the background, the author raises the problems of the research, such as: how does the discharge in collecting of market of retribution in Tabanan district and also how do the relation between market retribution with own source revenue of Tabanan district. This research uses empirical method and obtain the conclusion that market retribution has worked well and directly proportional with the own source revenue of Tabanan district.